Usury and The Hijrah from Ribā Movement in Indonesia: An Interpretative Phenomenological Inquiry - Wasyith, Wasyith; Kuswanjono, Arqom; Dumairy, Dumairy (Economica: Jurnal Ekonomi Islam, 2023)
Discussions about usury often spark long debates, as well as raise ambivalence. There has been a lot of literature highlighting the dynamics of this issue with various emphases. With the growing discourse on the establishment of Islamic economics in Indonesia, the Hijrah from Ribā movement originating from the grassroots is interesting to observe. However, there is still little literature that explores their personal world of experiences. This study seeks to understand how Islamic economic activists view usury. Three informants from the Special Region of Yogyakarta (DIY) Indonesia were selected for this study to be interviewed in a semi-structured manner. Interview transcripts were reviewed qualitatively using the IPA (Interpretative Phenomenological Analysis) approach. Data analysis revealed five superordinate themes: (1) business as usual, (2) a turning point, (3) learning process and role of the MUI fatwa, (4) post-hijrah spiritual experience, and (5) creative action: beyond debate. The findings of this study demonstrate the complexity of the psycho-social economic dimension, which has been neglected and is often ignored in the realm of modern positivism culture, which assumes economic reality to be autonomous and deterministic. Some methodological notes were also put forward to provide another facet in the development of Islamic economics research.